Characterization of Jatropha curcas honeys originating from the southern highlands of Madagascar. (July 2018) - Fröschle, M.; Horn, H.; Spring, O.
Abstract: Jatropha curcas, an entomophile Euphorphiaceae is an important bio-energy plant cultivated in some of the world's poorest countries. Commercial use of Jatropha honey could significantly improve the economic situation of plantations. This study evaluates the quality of 174 Jatropha honeys collected on Madagascar. Melissopalynology revealed a large pollen diameter of 87 μm and a verrucous exine causing under-representation of Jatropha pollen in monofloral honey. Characteristic physico-chemical parameters in the honeys were: pH 4.4; free acidity 18.2 meq/kg; electrical conductivity 756 μS cm −1 ; diastase number 12.9 DZ; total phenolic content 45 mg EGA /100 g; antioxidant capacity 56%. Fructose content (477 g/kg) was higher than glucose (326 g/kg) in all samples. Minor sugars were sucrose (16 g/kg), erlose (6 g/kg), turanose (5 g/kg), trehalose, maltose, and maltotriose (4 g/kg each). Proline (313.2 mg/kg) was the dominating free amino acid (49–79% of total amino acids), whereas asparagine, arginine and cysteine were not detected. Phorbolesters were not detected in any of the analyzed honey samples. Monofloral Jatropha honey meets the quality standards of the Codex Alimentarius in all aspects. Hence beekeeping on Jatropha plantations not only improves plant pollination and oil yield, but also generates additional income. Highlights: Jatropha curcas plantations on Madagascar provide a rich nectar source for honey bees. The chemical quality of Jatropha honey was analyzed and compared to other honeys. Jatropha honey proved to be of high quality and toxicologic uncritical for marketing. Honey production on Jatropha plantations could generate significant economic surplus.